Proceedings of the 1998 Multicultural Marketing Conference - Chebat, Jean-Charles.; Oumlil, A. Ben.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This volume includes the full proceedings from the 1998 Multicultural Marketing Conference held in Montreal, Canada. The focus of the conference and the enclosed papers is on marketing to various ethnic groups in both a US and global context. It presents papers on various multicultural issues across the entire spectrum of marketing activities and functions including marketing management, marketing strategy, and consumer behavior. Founded in 1971, the Academy of Marketing Science is an international organization dedicated to promoting timely explorations of phenomena related to the science of marketing in theory, research, and practice. Among its services to members and the community at large, the Academy offers conferences, congresses and symposia that attract delegates from around the world. Presentations from these events are published in this Proceedings series, which offers a comprehensive archive of volumes reflecting the evolution of the field. Volumes deliver cutting-edge research and insights, complimenting the Academy’s flagship journals, the Journal of the Academy of Marketing Science (JAMS) and AMS Review. Volumes are edited by leading scholars and practitioners across a wide range of subject areas in marketing science.
Multicultural Issues in Asia: Part I -- Multicultural Marketing Issues in Africa: Part I -- Cultural Effects on Marketing Strategies: Implications for Turkey -- Issues in Multicultural Market Segments -- Quality-of-Life Issues in Multicultural Marketing Contexts -- The Impact of Culture on Promotional Strategy -- New Approaches to the Understanding of Japanese Consumers and Marketing -- Multi-Cultural Issues in Advertising -- Entry Strategies in Emerging Markets of Asia and Africa -- African-American Consumers Behavior -- Multicultural Services Marketing -- Asian-American Markets: Strategic Issues and Insights -- Multicultural Marketing Issues in Africa: Part II -- Cultural Effects: Markets of Eastern European/Middle East Countries -- Marketing Ethics: Research in Progress -- Multicultural Issues in Retailing -- Multicultural Research Methodology -- Issues in Marketing to Hispanic-American Consumers -- Multicultural Issues in Business-to-Business Marketing -- Multicultural Perceptual Differences and Strategic Tools -- Multicultural Issues in Sales Management -- Healthcare Marketing -- Marketing to African-American Consumers -- Issues in Advertising and Marketing Research in Japan -- Canadian Perspectives on Culture and Ethnicity in Marketing Management -- Multicultural Issues in Asia: Part II -- Multicultural Marketing Issues in Africa: Work-in-Progress -- Business-to-Business Marketing: Work in Progress -- The Role of Culture in Marketing: Canadian Perspectives -- Multicultural European Issues in Marketing -- Multicultural Issues in Australia and New Zealand.
Keywords: Marketing; Leadership; Sales management; Marketing; Business Strategy/Leadership.; Sales/Distribution.